Electrolytic production of high purity lithium from low purity raw materials

Through the electrolytic system of solid electrolytes, garnet-type oxides are used as electrolytes to solve the cost and time problems of purifying lithium from low-purity lithium resources, achieving efficient and economical lithium purification, and reducing the working temperature.

CN113811640BActive Publication Date: 2025-03-25JIANGSU XINLIYUAN TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN201980092700.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-13
Publication Date
2025-03-25
Estimated Expiration
2039-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and economically purify lithium from low-purity lithium resources, and conventional methods require high temperatures, resulting in cost and time challenges.

Method used

An electrolytic system using a solid electrolyte is used to electrolyze a melting composition containing lithium salts, and garnet-type oxides are used as a solid electrolyte to allow lithium ions to pass through and prevent other atoms, achieving efficient purification of lithium.

Benefits of technology

It significantly reduces the cost and time of lithium purification, can effectively extract high-purity lithium from low-purity lithium resources, and reduces the working temperature, avoiding the generation of corrosive gases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113811640B_ABST
    Figure CN113811640B_ABST
Patent Text Reader

Abstract

The present invention provides an apparatus and method for purifying lithium from lithium salt (including low-concentration lithium salt).The molten composition containing lithium salt is electrolyzed using an anode in contact with the molten composition and a cathode separated from the molten composition by a solid electrolyte capable of conducting lithium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Lithium has the lowest density among metals under standard conditions, a property that makes it attractive for use in light alloys. Lithium is also widely used as a chemical reagent for the production of organolithium. In recent decades, lithium-ion batteries (LIBs) for portable electronics, electric vehicles, and large energy systems have experienced explosive growth, leading to a significant increase in lithium consumption. Although commercial LIBs do not currently use metallic lithium directly as an electrode material, lithium metal anodes are essential for the next generation of rechargeable batteries with high energy density, such as all-solid-state lithium metal batteries and lithium-sulfur batteries. The demand for metallic lithium is expected to grow significantly in the coming decades. The sustainability of lithium resources has received increasing attention from both academic research and industry. Recovering lithium from low-grade salt lakes and seawater may provide a practical solution for the sustainable development of lithium resources.

[0002] Improved methods of purifying lithium from national resources are needed, especially those with low-purity lithium. SUMMARY OF THE INVENTION

[0004] In some embodiments, the present invention provides an apparatus and method for purifying lithium from lithium salts (including lithium salts with low concentrations of lithium salts). This method does not require the purification of lithium salts from natural sources first. In addition, the operating temperature is significantly reduced. Therefore, compared with conventional methods, the present technology significantly reduces the cost and time of lithium purification.

[0005] Therefore, according to one embodiment of the present invention, there is provided an electrolysis method, comprising electrolyzing a molten composition containing a lithium salt, wherein an anode is in contact with the molten composition, and a cathode is separated from the molten composition by a solid electrolyte capable of conducting lithium ions, wherein the solid electrolyte allows lithium ions but does not allow other atoms to pass through.

[0006] In some embodiments, the lithium-ion conducting solid electrolyte comprises a garnet-type oxide, such as tantalum-doped Li 7 La 3 Zr 2 O 12 Examples of garnet-type oxides include Li 7-x La 3 Ta x Zr 2-x O 12 , wherein x is 0.1 to 1.0, or preferably 0.4 to 0.6. Specific examples include but are not limited to Li 6.4 La 3 Ta 0.6 Zr 1.4 O 12 , Li 6.5 La 3 Ta0.5 Zr 1.5 O 12 and Li 6.6 La 3 Ta 0.4 Zr 1.6 O 12 .

[0007] The solid electrolyte can be in any physical form, such as in the form of a cylinder or a plate, as long as it separates the molten composition from the cathode. In some embodiments, the cross-sectional thickness of the solid electrolyte is 0.05 cm to 0.6 cm, preferably 0.15 cm to 0.4 cm. In some embodiments, the solid electrolyte has a relative density greater than 97%.

[0008] In some embodiments, the lithium salt in the molten composition comprises LiCl. In some embodiments, the molten composition comprises less than 99.7%, less than 97%, less than 50%, less than 1%, or less concentration of a lithium salt (e.g., LiCl). In some embodiments, the molten composition further comprises an aluminum salt, such as AlCl 3 The molar ratio of lithium to aluminum is preferably from 20:1 to 1:1.

[0009] In some embodiments, an apparatus for purifying lithium is also provided, comprising: an electrolyte chamber for storing a molten electrolyte; an anode comprising metallic aluminum, placed in contact with the electrolyte when included; a cathode chamber for storing molten lithium; a solid electrode, placed in contact with the molten lithium when included; and a solid electrolyte located between the electrolyte chamber and the cathode chamber, wherein the solid electrolyte allows lithium ions to pass without allowing any other atoms to pass through. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The drawings described herein are for illustration purposes only. The drawings are not intended to limit the scope of the present invention.

[0011] Figure 1 An electrolysis apparatus for purifying lithium is described.

[0012] Figure 2a-b Comparison of a conventional electrolysis device (a) and a novel electrolysis device (b) that can be used to purify lithium. a. Schematic diagram of a conventional electrolysis device. b. Schematic diagram of a novel electrolysis device using LLZTO solid electrolyte.

[0013] Figure 3a-d The electrolysis device of the present invention and its physical / electrical properties are illustrated. a. Schematic diagram of the electrolysis device. The stainless steel housing is used as the anode current collector and the stainless steel rod is used as the cathode current collector. b. Digital photo of the electrolysis device. c. Digital photo of the LLZTO solid electrolyte tube. d. Ionic conductivity of the LLZTO solid electrolyte at 40°C to 280°C.

[0014] Figure 4a-d The production of lithium by electrolysis is shown. a. Voltage distribution during electrolysis. The electrolyte consists of LiCl (1.09 g), NaCl (0.25 g), KCl (0.32 g), MgCl 2 (0.41 g) and AlCl 3 (1.14 g). The mass fraction of lithium ions is 5.5%. The efficiency of the electrolysis process in ba. c. The voltage distribution of the electrolysis process. The electrolyte consists of LiCl (1.27 g), LiBr (0.087 g), LiI (0.134 g), Na 2 SO 4 (0.142 g) and AlCl 3 (1.33 g) composition. The efficiency of the electrolysis process in dc. The current density for both electrolysis processes was 5 mA cm -2 . The operating temperature is 240℃.

[0015] Figure 5a-b The extraction of lithium from a molten salt with low lithium ion concentration is shown. a. Voltage distribution during electrolysis. The electrolyte consists of LiCl (0.01 g), NaCl (1.75 g), KCl (0.30 g), MgCl 2 (0.57 g) and AlCl 3 (4.00 g). The current density is 1 mA cm -2 , the operating temperature is 240°C. b. The mass change of lithium ions in the electrolyte before and after the electrolysis process.

[0016] Figure 6a-b The production of low-cost electrolytic lithium is shown. a. Voltage profile during electrolysis. The electrolyte consists of industrial grade LiCl (1.41 g) and AlCl 3 (0.57 g) composition. The efficiency of the electrolysis process in ba. The current density of the electrolysis process is 5 mA cm -2 . The operating temperature is 240℃.

[0017] Figure 7 A scanning electron microscope image of the LLZTO solid electrolyte is shown.

[0018] Figure 8 shows the X-ray diffraction pattern of LLZTO solid electrolyte.

[0019] Reference will now be made in detail to certain embodiments of the present invention. Although certain embodiments of the present invention have been described, it should be understood that it is not intended to limit the embodiments of the present invention to the disclosed embodiments. On the contrary, reference to embodiments of the present invention is intended to cover substitutions, modifications and equivalents that may be included within the spirit and scope of embodiments of the present invention as defined by the appended claims.

[0020] Detailed description

[0021] For the purpose of the following description, it should be understood that the embodiments provided by the present invention may adopt various optional changes and step sequences, unless explicitly indicated to the contrary. In addition, except in the examples or otherwise indicated, all representations, such as the numbers of the amount of the components used in the specification and claims, should be understood to be modified by the term "about" in all cases. Therefore, unless explicitly indicated to the contrary, the numerical parameters described in the following specification and the attached claims are approximate values ​​and may vary according to the desired characteristics to be obtained. At least, it is not intended to limit the application of the doctrine of equivalents to the scope of the claims, and each numerical parameter should at least be interpreted according to the number of reported significant figures by applying ordinary rounding techniques.

[0022] Although the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.

[0023] Furthermore, it should be understood that any numerical range described herein is intended to include all sub-ranges contained therein. For example, a range of "1 to 10" is intended to include all sub-ranges between (and including) the stated minimum value of about 1 and the stated maximum value of about 10, i.e., having a minimum value equal to or greater than about 1 and a maximum value equal to or less than about 10. Also, in this application, the use of "or" means "and / or" unless otherwise specifically stated, even though "and / or" may be explicitly used in certain circumstances.

[0024] The industrial production of lithium metal relies on the electrolysis of high-purity lithium chloride. Therefore, the high complexity and cost of obtaining high-purity lithium chloride severely limits the sustainable production of lithium. In some embodiments, the present invention provides new devices and methods that can produce high-purity lithium from low-purity lithium chloride at low cost, without the need to prepare the high-purity lithium chloride required by conventional processes.

[0025] In some embodiments, the new method utilizes an electrolytic system with a solid electrolyte. In some embodiments, the solid electrolyte can conduct lithium ions and allow lithium ions to pass through. However, the solid electrolyte does not allow other atoms (particularly cations and other metal atoms) to pass through.

[0026] For example, one embodiment provides an electrolysis method, comprising electrolyzing a molten composition comprising a lithium salt, wherein an anode is in contact with the molten composition and a cathode is separated from the molten composition by a solid electrolyte. The cathode may include molten lithium, the total amount of which will increase during the electrolysis process.

[0027] Taking advantage of the high lithium ion selectivity of the solid electrolyte, this method is able to extract high-purity lithium directly from high-purity or low-purity lithium sources. As shown in the experimental examples, high-purity lithium was obtained from mixed salts with ultra-low lithium concentrations (e.g., 0.06 wt.%), indicating that even natural salts from brine can be used as a sustainable source for producing high-purity electrolytic lithium.

[0028] The new technique described here has at least two significant advantages. First, it demonstrates that high purity lithium can be obtained at low cost. The cost of obtaining electrolytic lithium as described herein is estimated to be only 20% of that of conventional metallic lithium methods. Second, in this technique, lower electrolysis temperatures can be used than in conventional electrolysis processes. More interestingly, when AlCl 3 When added to the molten composition, the operating temperature of the electrolysis process can be reduced from 400°C to 240°C.

[0029] Considering that nearly 90% of recoverable lithium resources are deposited in brine, recovering lithium from brine is one of the most important methods to obtain lithium metal. The industrial production of metallic lithium requires the electrolysis of molten LiCl-KCl salts extracted and purified from natural resources (Figure 2a). In this process, molten LiCl is used as the raw material source and ion-conductive electrolyte for lithium electrolysis, so high-purity LiCl and KCl are required to ensure the purity of the lithium metal product. Otherwise, impurity cations, such as Na + Mg 2+ and Al 3+ It will be deposited on the cathode together with lithium metal (Figure 2a). In this process, the purity of LiCl should be higher than 99.3% to produce high-purity lithium metal.

[0030] The purification of LiCl is very complicated and expensive. In particular, the high Mg / Li ratio of some salt lake brines makes it difficult to recover lithium. In addition, the LiCl-KCl mixed salt has a high melting point of more than 350°C. Therefore, the operating temperature is higher than 400°C. In addition, chlorine gas is produced at the anode, corroding the equipment. However, this technology does not have such disadvantages.

[0031] In some embodiments, the present invention also provides an apparatus suitable for use in the method of the present invention. In one embodiment, an apparatus for purifying lithium is provided, comprising an electrolyte chamber for storing molten electrolyte; an anode containing (or at least partially covered with) metallic aluminum, placed in contact with the electrolyte when included; a cathode chamber for storing molten lithium; a solid electrode, placed in contact with the molten lithium when included; and a solid electrolyte located between the electrolyte chamber and the cathode chamber. In some embodiments, the solid electrolyte allows lithium ions to pass without allowing any other atoms to pass.

[0032] Figure 1A schematic diagram of an embodiment of an electrochemical device suitable for the method of the present invention is provided, in which a molten electrolyte / composition and molten lithium are filled. The device includes a cathode 102 comprising lithium metal or a lithium metal alloy, and an anode which is a molten composition 104 comprising a lithium salt or a cylinder 101 electrically connected to the molten composition. A solid electrolyte in the form of a tube 103 separates the cathode 102 and the molten composition 104. In addition, the device may include a cathode current collector 105 in contact with the cathode 102 and electrically connected to the positive electrode 106. The molten composition 104 is in contact with the cylinder 101 which may also serve as an anode current collector.

[0033] The solid electrolyte may be in the form of an open-ended cylinder or a closed-end cylinder. One or both open ends of the cylinder may be sealed with a material capable of maintaining the integrity of the seal under operating conditions (e.g., temperatures below 600°C) and during temperature cycling from 0°C to 600°C and when exposed to molten lithium, molten lithium alloys, and molten lithium salts.

[0034] Apart from Figure 1 In addition to the configuration shown, other configurations of the electrochemical device are possible. For example, in Figure 2b, the anode, solid electrolyte and / or cathode may be in the form of parallel plates separating the anode and cathode.

[0035] The solid electrolyte may include a material that is capable of conducting lithium ions. Preferably, the solid electrolyte does not allow other atoms or ions to pass through, particularly other metal atoms or ions that may contaminate the purified lithium. The solid electrolyte maintains the separation between the anode and cathode during use. For example, the solid electrolyte may include a lithium ion conducting oxide, a lithium ion conducting phosphate, a lithium ion conducting sulfide, or a combination of any of the foregoing.

[0036] Examples of suitable lithium ion conducting oxides include garnet-type oxides, lithium super ion conductor (LISICON)-type oxides, perovskite-type oxides, and combinations of any of the foregoing.

[0037] The lithium ion conducting oxide may comprise a garnet-type oxide, such as tantalum-doped Li 7 La 3 Zr 2 O 12 The garnet-type oxide may contain Li 7-x La 3 Zr 2-x Ta x O 12 , wherein x may be, for example, from 0.1 to 1.0, from 0.2 to 0.9, from 0.3 to 0.8, or from 0.4 to 0.6.

[0038] Garnet-type oxides may include Li 6.5 La3 Zr 1.5 Ta 0.5 O 12 The garnet-type oxide may include Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (Also referred to herein as "LLZTO"). The garnet-type oxide may include Li 6.6 La 3 Zr 1.6 Ta 0.4 O 12 The garnet-type oxide may include Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 .

[0039] Suitable lithium superion conductor (LISICON) type oxides include, for example, Li 14 ZnGe 4 O 16 Suitable perovskite oxides include, for example, Li 3x La 2 / 3-x TiO 3 and La (1 / 3)-x Li 3x NbO 3 , where x can be, for example, 0.1 to 1.0, 0.2 to 0.9, 0.3 to 0.8, or 0.4 to 0.7.

[0040] Examples of suitable lithium ion conducting phosphates include Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 、LiZr 2 (PO 4 ) 3 、LiSn 2 (PO 4 ) 3 and Li 1+x Al x Ge 2-x (PO 4 ), wherein x can be, for example, 0.1 to 1.0, 0.2 to 0.9, 0.3 to 0.8, or 0.4 to 0.7.

[0041] Examples of suitable lithium ion conducting sulfides include Li 2 S-SiS 2 , Li 2 S-GeS 2 -P2 S 5 and combinations thereof.

[0042] The LLZTO solid electrolyte provided by the present invention may have a density greater than 96%, greater than 97%, greater than 98% or greater than 99%. For example, the LLZTO solid electrolyte may have a density of 96% to 99.9%, 97% to 99.9%, 98% to 99.9% or 98% to 99%.

[0043] The LLZTO solid electrolyte provided by the present invention can be prepared by high-pressure cold isostatic pressing and spray granulation.

[0044] The LLZTO solid electrolyte provided by the present invention may have a cross-sectional thickness of, for example, 0.1 cm to 0.6 cm, 0.15 cm to 0.5 cm, or 0.2 cm to 4 cm.

[0045] In some embodiments, the cathode comprises molten lithium. The molten lithium salt in the anode may include any one or more lithium salts obtainable from artificial or natural resources. In some embodiments, the lithium salt comprises LiCl.

[0046] As mentioned above, the purity of LiCl need not be very high as required in conventional techniques. In certain embodiments, the molten composition comprises less than 99.7% lithium salt. In certain embodiments, the molten composition comprises less than 99.5%, 99%, 98%, 97%, 95%, 90%, 80%, 75%, 60%, 50%, 40%, 30%, 20%, 10%, 5%, 1%, 0.5%, 0.1% or 0.01% lithium salt. In certain embodiments, the molten composition comprises less than 99.7%, 99.5%, 99%, 98%, 97%, 95%, 90%, 80%, 75%, 60%, 50%, 40%, 30%, 20%, 10%, 5%, 1%, 0.5%, 0.1% or 0.01% LiCl.

[0047] In some embodiments, the molten composition further comprises an aluminum salt, such as AlCl 3. The aluminum salt may be naturally present in the lithium salt or may be added before or during electrolysis. In some embodiments, the molar ratio of lithium to aluminum in the molten composition is from 20:1 to 1:1. In some embodiments, the molar ratio of lithium to aluminum in the molten composition is from 20:1 to 2:1, 20:1 to 3:1, 20:1 to 4:1, 20:1 to 5:1, 20:1 to 6:1, 20:1 to 7:1, 20:1 to 8:1, 19:1 to 2:1, 19:1 to 3:1, 19:1 to 4:1, 19:1 to 5:1, 19:1 to 6:1, 19:1 to 7:1, 19:1 to 8:1, 18:1 to 2:1, 18:1 to 3:1, 18:1 to 4:1, 18:1 to 5:1, 18:1 to 6:1, 18:1 to 7:1, 18:1 to 8:1 :1 to 8:1, 17:1 to 2:1, 17:1 to 3:1, 17:1 to 4:1, 17:1 to 5:1, 17:1 to 6:1, 17:1 to 7:1, 17:1 to 8:1, 16:1 to 2:1, 16:1 to 3:1, 16:1 to 4:1, 16:1 to 5:1, 16:1 to 6:1, 16:1 to 7:1, 16:1 to 8:1, 15:1 to 2:1, 15:1 to 3:1, 15:1 to 4:1, 15:1 to 5:1, 15:1 to 6:1, 15:1 to 7:1, 15:1 to 8:1, 14:1 to 2:1, 14:1 to 3:1, 14:1 to 4:1, 14:1 to 5:1, 14:1 to 6:1, 14:1 to 7:1, 14:1 to 8:1, 13:1 to 2:1, 13:1 to 3:1, 13:1 to 4:1, 13:1 to 5:1, 13:1 to 6:1, 13:1 to 7:1, 13:1 to 8:1, 12:1 to 2:1, 12:1 to 3:1, 12:1 to 4:1, 12:1 to 5:1, 12:1 to 6:1, 12:1 to 7:1, 12:1 to 8:1, 11:1 to 2:1, 11:1 to 3:1, 11:1 to 4:1 :1, 11:1 to 5:1, 11:1 to 6:1, 11:1 to 7:1, 11:1 to 8:1, 10:1 to 2:1, 10:1 to 3:1, 10:1 to 4:1, 10:1 to 5:1, 10:1 to 6:1, 10:1 to 7:1, 10 to 8:1, 9:1 to 2:1, 9:1 to 3:1, 9:1 to 4:1, 9:1 to 5:1, 9:1 to 6:1, 9:1 to 7:1, 9:1 to 8:1, 8:1 to 2:1, 8:1 to 3:1, 8:1 to 4:1, 8:1 to 5:1, 8:1 to 6:1, or 8:1 to 7:1.

[0048] The cathode current collector may include any suitable material, such as stainless steel, copper, copper alloys, carbon, graphite, or a combination of any of the foregoing. The cathode current collector may be inert when exposed to molten lithium and / or molten lithium alloys.

[0049] The anode current collector may include any suitable material, such as stainless steel, copper, copper alloys, carbon, graphite, or a combination of any of the foregoing. In some embodiments, the anode current collector includes metallic aluminum, which may be present on a surface in direct contact with the molten composition containing the lithium salt.

[0050] Under operating conditions, the electrochemical device used in these methods can be heated above the melting temperature to melt the lithium or lithium salt during operation. For example, under operating conditions, the temperature of the battery can be below 600°C, below 500°C, below 400°C, below 300°C, or below 250°C, and above the melting point of lithium and / or lithium salt.

[0051] During use, a sealant may be used to retain the anode / cathode materials. The sealant may be in the form of a paste or a gasket. It is expected that the gasket material will not degrade and maintain a viable seal under the conditions of use of the electrochemical cell. Suitable gasket materials will not significantly degrade after long-term exposure to the anode and cathode materials in the temperature range of 200° C. to 600° C. or 200° C. to 300° C. Suitable gasket materials include elastomers such as silicones, perfluoroethers, polytetrafluoroethylene, and polyepoxides.

[0052] In some embodiments, the electrochemical device is also connected to or equipped with a heating element for providing heat to the device. Example

[0053] Example 1

[0054] One-step electrolytic production of high-purity lithium from low-purity sources using solid electrolytes

[0055] This embodiment describes a method using a solid electrolyte (e.g., garnet-type Li 6.4 La 3 Ta 0.6 Zr 1.4 O 12 (LLZTO) as a separator between two molten electrodes, a new method for preparing high-purity electrolytic lithium from low-cost and low-purity LiCl. Taking advantage of the high lithium ion selectivity of the solid electrolyte, this example directly obtains high-purity metallic lithium (lithium content>99.7 wt.%) by electrolyzing low-purity LiCl (~95 wt.%). This example further demonstrates the extraction of lithium from mixed salts with low lithium concentrations (0.06 wt.%), indicating that natural salts from brines can be used as a sustainable source for producing electrolytic lithium.

[0056] The new method for extracting metallic lithium from LiCl offers at least two significant advantages. First, it shows that high-purity lithium can be obtained at low cost. The cost of electrolytic lithium is estimated to be only 20% of that of existing metallic lithium methods. Second, in the new method, lower electrolysis temperatures can be used than in conventional processes. More interestingly, when AlCl is added, the 3 When the temperature of the electrolysis process is reduced from 400°C to 240°C,

[0057] method

[0058] The process of garnet-type LLZTO electrolyte. 2 CO 3 (Sinopharm Chemical Reagent Co.,Ltd, 99.99%), La 2 O 3 (Sinopharm Chemical Reagent Co., Ltd, 99.99%), ZrO 2 (Aladdin, 99.99%) and Ta 2 O 5 (Ourchem, 99.99%) 6.5 La 3 Zr 0.5 Ta 1.5 O 12 The molar ratio is fully mixed (add 20% excess La 2 O 3 ) and then heated at 900 °C for 6 h. The resulting powder was thoroughly ball milled for 12 h and then pressed into a U-tube at 220 MPa cold isostatic pressing for 90 s. The tube covered with the same master powder was then annealed at 1140 °C for 16 h in air. All heat treatments were performed in an alumina crucible (>99% Al 2 O 3 ), the crucible is covered with an alumina cover.

[0059] Construction of the electrolysis device. First, metallic lithium (0.1 g) was placed in the LLZTO tube and then moved into a box furnace (MTI) to melt it at 300°C for 1 hour. The mixed salt was then placed in a stainless steel-aluminum shell and moved into a box furnace (MTI) at 150°C for 60 minutes to melt it into a liquid state. The above LLZTO tube containing liquid lithium was placed in a molten salt at 240°C. A stainless steel rod with a diameter of 1 mm was inserted into the liquid lithium as a cathode current collector. The entire assembly process was carried out in an argon glove box.

[0060] Electrochemical measurements. Electrochemical tests of the electrolysis process were performed in a box furnace (MTI) at 240 °C. All devices were loaded into the electrolysis test (LAND 2001 CT battery tester) and charged at 1 mA / cm 2 Up to 10 mA / cm 2 Charged at a current density of .

[0061] Characterization. The relative density of the LLZTO tubes was measured using the Archimedean method. The microstructure of all samples was investigated by scanning electron microscopy using a MERLIN Compact Zeiss scanning electron microscope. α X-ray diffraction (XRD) patterns of the fabricated materials were evaluated by a D / max-2500 diffractometer (Rigaku, Japan) with a radiation source. Impedance spectroscopy measurements were performed using a broadband dielectric spectrometer (NOVOCOOL) (frequency range: 10 MHz - 40 Hz; AC voltage: 10 mV; temperature: 40-280 °C). The purity of the electrolytic lithium and commercial lithium was determined by ICP-MS measurements (ELAN-DRC-e).

[0062] Results and Analysis

[0063] This example demonstrates a new method for producing electrolytic lithium based on lithium ion solid electrolyte. 6.4 La 3 Ta 0.6 Zr 1.4 O 12 (LLZTO) ceramics as solid electrolyte and separator, low purity molten LiCl-AlCl 3 Salt is used as the raw material for electrolysis to obtain high-purity electrolytic metallic lithium (Figure 2b).

[0064] The results show that industrial-grade lithium chloride (~95 wt.%) can be used as a raw material for the production of high-purity electrolytic lithium (>99.7 wt.%). The cost of industrial-grade LiCl is much lower than that of high-purity LiCl. Therefore, the cost of metallic lithium produced by this method is estimated to be only 20% of the international metallic lithium price. The extraction of lithium from mixed salts with low concentrations of LiCl (<0.4 wt.%) has also been confirmed. The concentration of lithium ions (0.06 wt.%) is the same as that of natural salts obtained from brine. At this ultra-low concentration, more than 80% of the lithium ions are reduced to metallic lithium, indicating that this method can directly extract lithium from natural salts in brine.

[0065] The schematic diagram of the electrolysis device is shown in Figure 3a, and its digital photo is shown in Figure 3b. As an important component of the electrolysis device, the LLZTO ceramic tube (Figures 3c, 7, and 8) exhibits a high conductivity of 38 mS cm at 240 °C. -2The high electrical conductivity is about 100 times higher than that at room temperature (Figure 3d). The ionic conductivity of the solid electrolyte is not a problem in the electrolysis system. The LLZTO ceramic tube also has a relative density of ~99%, which prevents leakage of the liquid electrode. Since both the cathode (molten lithium) and the electrolyte (molten salt) are liquids, the interface between the solid electrolyte and the cathode or electrolyte is a liquid-solid interface. Therefore, during the electrolysis process, the interface maintains good contact. The above facts show that LLZTO tubes can be used as electrolytes and separators for electrolysis devices.

[0066] LLZTO High selectivity of solid electrolytes

[0067] In order to demonstrate the high selectivity of LLZTO ceramic tubes, LiCl, NaCl, KCl, MgCl 2 and AlCl 3 A mixed salt composed of sodium ions and potassium ions is used as an electrolyte. Sodium ions and potassium ions are common impurities in LiCl raw materials. In conventional methods, when LiCl is extracted from brine as a raw material, magnesium ions and lithium ions are difficult to separate. In the method of the present invention, AlCl is added 3 To lower the melting point of the mixed salt. Metal aluminum is also used as an anode, so the electrolysis reaction equation can be expressed as:

[0068] Al + 3Li + + 4Cl - → 3Li + [AlCl 4 ] - (1)

[0069] Only lithium ions can penetrate the solid electrolyte (Figure 2b), and other cations cannot participate in the electrolysis reaction. A small amount of commercial lithium was used to connect the LLZTO ceramic tube and the current collector. The voltage distribution of the electrolysis process is shown in Figure 4a. The initial electrolysis voltage was about ~1.85V and remained stable until the capacity reached 500 mAh. The cut-off voltage was 2V and the final capacity was 583.5 mAh. In order to prevent corrosion of the stainless steel casing by the molten salt, the cut-off voltage was set to 2V. If 100% of the capacity of 583.5 mAh was due to lithium metal deposition, this would translate into 0.151g of lithium metal. In practice, 0.145g of metallic lithium was obtained with a lithium metal Coulombic efficiency of 96.0% (Figure 4b). This difference may be due to weighing errors and a small amount of side reactions. The increase in electrolysis voltage in the final stage was caused by the decrease in lithium ion concentration in the electrolyte. Based on the initial mass of LiCl in the mixed salt (1.09 g), about 82% of lithium was extracted in this example.

[0070] In order to test the purity of the obtained electrolytic lithium, inductively coupled plasma mass spectrometry (ICP-MS) measurements were performed. Commercial metallic lithium with a purity of 99.7% was determined by the same method for comparison. As shown in Table 1, the purity of commercial lithium and electrolytic lithium is almost the same. The concentration of impurities (sodium, potassium, magnesium, aluminum) in the electrolytic lithium is very low and similar to that of commercial lithium. The concentrations of lanthanum, tantalum and zirconium elements are extremely low (<0.01ppm), indicating that the LLZTO solid electrolyte has a high chemical stability to molten lithium. It is worth noting that the obtained electrolytic lithium has a purity of about 99.7%. Considering the initial mass fraction of lithium ions in the molten salt (5.5%), the lithium ion concentration increased by more than 17 times after electrolysis. The obtained high-purity lithium-ion battery confirms the high selectivity and high quality of the LLZTO solid electrolyte.

[0071] Table 1. ICP-MS measurement results of electrolytic lithium, commercial lithium and ultrapure water

[0072]

[0073] Other anions, including Br - ,I - and SO 4 2- was also added to the electrolyte, and the effect of anions on the electrolysis process was tested. The voltage distribution of the electrolysis process is shown in Figure 4c. The electrolysis voltage stabilized at 1.75V. When the capacity reached 430 mAh, the electrolysis process stopped. If 100% of the capacity was due to lithium metal deposition, nearly 50% of the lithium ions in the mixed salt would be reduced to obtain 0.112g of lithium. In practice, 0.107g of metallic lithium was obtained, which provided a Coulombic efficiency of 95.5% for lithium metal deposition (Figure 4d). According to the ICP-MS measurement results (Table 2), the effect of anions on the purity of the obtained lithium was negligible. The chlorine element mainly originated from the ultrapure water used for ICP-MS determination.

[0074] Table 2. ICP-MS measurement results of electrolytic lithium, commercial lithium and ultrapure water

[0075]

[0076] Extracting lithium from low-concentration lithium ion raw materials

[0077] Extracting lithium from brine containing low concentrations of lithium ions is a challenging task. In order to test the extraction ability of the solid electrolyte, a mixed salt was prepared in this example according to the cation ratio of the salt lake brine. The initial concentration of lithium ions was only 0.06wt%, which is the average level of several salt lakes in China. As shown in Figure 5a, the final capacity was 7.77 mAh, slightly higher than the theoretical value (6.28 mAh). This difference is mainly caused by side reactions. After electrolysis, the residual salt was dissolved in 100 mL of ultrapure water for ICP-MS measurement. 2.58 ppm of lithium remained in the solution, indicating that 84.2% of lithium ions were extracted to form metallic lithium (Figure 5b). The purity of the obtained lithium metal is the same as that of commercially available high-purity lithium metal (Table 3). After electrolysis, the concentration of lithium increased by more than 1500 times. This result proves that our solid electrolyte method can directly extract lithium from natural salt.

[0078] Table 3. ICP-MS measurement results of electrolytic lithium obtained from mixed salts with low lithium ion concentration

[0079]

[0080] Low-cost production of lithium electrolyte

[0081] By using a lithium-based solid electrolyte as a lithium-ion selective layer, high-purity metallic lithium can be produced from low-purity LiCl containing large amounts of sodium, magnesium, potassium, and aluminum ions. Since low-purity LiCl is relatively cheap, using it as a raw material has the potential to significantly reduce the production cost of electrolytic lithium. To illustrate the potential of this approach, industrial-grade LiCl (~95 wt.%) and AlCl 3 (molar ratio 8:1) as electrolyte to produce electrolytic lithium. The electrolysis voltage distribution is shown in Figure 6a. The electrolysis voltage is stable at ~1.7V. In order to avoid the generation of Al 2 Cl 6 Gas, when LiCl and AlCl in the electrolyte 3 When the molar ratio of lithium ions drops to 1:1, the electrolysis process is stopped. In principle, 65.6% of the lithium ions will be reduced to metallic lithium, and 0.156g of metallic lithium is obtained. In practice, 0.148g of metallic lithium was obtained, which is 94.8% of the theoretical value (Figure 6b). The concentrations of common impurities in the production of metallic lithium were determined, and the results are shown in Table 4. There is no significant difference in the impurity concentrations between electrolytic lithium and commercial lithium. The most exciting result is that the magnesium impurity content in the electrolytic lithium metal is very low. Due to the similar radii of magnesium and lithium ions, it is difficult to separate magnesium from lithium by traditional separation methods. However, in this case, due to its divalent charge, Mg 2+ Ions diffuse very slowly in lithium solid electrolytes. Taking into account the impurities in ultrapure water, the resulting electrolytic lithium purity is about 99.7%.

[0082] Table 4. ICP-MS measurement results of electrolytic lithium, commercial lithium and ultrapure water

[0083]

[0084] This example demonstrates a new method for producing electrolytic lithium using solid electrolytes. Due to the high selectivity of solid electrolytes, low-purity LiCl containing a large amount of other metal cations can be used as a raw material to produce high-purity metallic lithium. Compared with the high-purity LiCl used in the traditional electrolytic method to produce high-purity lithium, the price of low-purity industrial-grade LiCl is much lower. This method greatly reduces the cost of electrolytic lithium. In addition, adding AlCl to the electrolyte 3 Effectively reduces the operating temperature of the electrolysis device and avoids corrosive Cl 2 Most notably, the high selectivity of lithium-ion solid electrolytes has an outstanding separation effect on those challenging impurities (such as magnesium ions). Therefore, salt lake brine with a high magnesium / lithium ratio can be used as a low-cost lithium recovery source, further reducing the cost of electrolytic lithium. This embodiment realizes the extraction of lithium from mixed salts with ultra-low concentrations of lithium ions, making it possible to recover lithium from natural salts.

[0085] Finally, it should be noted that there are alternative methods of implementing the embodiments disclosed in the present invention. Therefore, the present embodiments are considered to be illustrative rather than restrictive. In addition, the claims are not limited to the details given in the present invention, and are entitled to their full scope and equivalent scope.

Claims

1. A method for preparing metallic lithium by electrolysis, comprising electrolyzing a molten composition comprising a lithium salt, an aluminum salt and an impurity salt to obtain metallic lithium having a purity greater than or equal to 99.7% by weight, in, The molten composition comprises less than 95 wt % of a lithium salt, the molar ratio of lithium to aluminum in the molten composition is 20:1 to 1:1, and the impurity salt comprises at least one of a potassium salt, a sodium salt, and a magnesium salt; wherein an anode covered with metallic aluminum is in contact with the molten composition, and a cathode containing molten lithium is separated from the molten composition by a solid electrolyte capable of conducting lithium ions; The solid electrolyte allows lithium ions but does not allow other cations or other metal atoms to pass through, and the solid electrolyte is a garnet oxide Li 7-x La3Ta x Zr 2-x O 12 , wherein x is 0.4 to 0.6, and the relative density of the solid electrolyte is 97% to 99.9%.

2. The method according to claim 1, wherein the garnet-type oxide comprises Li 6.4 La3Ta 0.6 Zr 1.4 O 12 , Li 6.5 La3Ta 0.5 Zr 1.5 O 12 or Li 6.6 La3Ta 0.4 Zr 1.6 O 12 .

3. The method according to claim 1, wherein the solid electrolyte is in the form of a cylinder or a plate.

4. The method according to claim 3, wherein the cross-sectional thickness of the solid electrolyte is 0.05 cm to 0.6 cm.

5. The method of claim 3, wherein the cross-sectional thickness of the solid electrolyte is 0.15 cm to 0.4 cm.

6. The method according to any one of claims 1 to 5, wherein the lithium salt is LiCl, the aluminum salt is AlCl3, and the impurity salts are NaCl, KCl and MgCl2.

7. The method of any one of claims 1-5, wherein the molten composition comprises less than 80% lithium salt.

8. The method of claim 7, wherein the molten composition comprises less than 70% lithium salt.

9. The method of claim 7, wherein the molten composition comprises less than 50% lithium salt.

10. The method of claim 7, wherein the molten composition comprises less than 1% lithium salt.

11. A device for preparing metallic lithium by electrolysis, comprising: an electrolyte chamber for storing a molten electrolyte comprising a lithium salt, an aluminum salt, and an impurity salt; an anode comprising metallic aluminum placed in contact with the molten electrolyte; a cathode chamber for storing molten lithium; a solid electrode placed in contact with the molten lithium; and a solid electrolyte located between the electrolyte chamber and the cathode chamber, Wherein, the solid electrolyte is garnet-type oxide Li 7-x La3Ta x Zr 2-x O 12 , wherein x is 0.4 to 0.6, and the relative density of the solid electrolyte is 97% to 99.9%; The solid electrolyte allows lithium ions but does not allow any other cations or other metal atoms to pass through, so that a molten composition containing lithium salt, aluminum salt and impurity salt is electrolyzed to produce metallic lithium with a purity greater than or equal to 99.7% by weight, wherein the molten composition contains less than 95% by weight of lithium salt, the molar ratio of lithium to aluminum in the molten composition is 20:1 to 1:1, and the impurity salt includes at least one of potassium salt, sodium salt and magnesium salt.

12. The device of claim 11, wherein the solid electrolyte is in the form of a cylinder.

13. The device of claim 12, wherein the cathode chamber is inside the cylinder and the electrolyte chamber is outside the cylinder.

14. The apparatus of claim 11, wherein the apparatus further comprises a channel positioned to contact the molten lithium and driven to remove the molten lithium from the cathode chamber.

15. The device of claim 11, wherein the device further comprises a heating element to provide heat to the molten electrolyte and / or the molten lithium.

16. The device according to claim 11, wherein the garnet-type oxide comprises Li 6.4 La3Ta 0.6 Zr 1.4 O 12 , Li 6.5 La3Ta 0.5 Zr 1.5 O 12 or Li 6.6 La3Ta 0.4 Zr 1.6 O 12 .

Citation Information

Patent Citations

  • Method of preparing metallic lithium by one-step fusion electrolysis of lithium salt

    CN103205774A

  • Method for electrochemically producing lithium

    CN1269430A

  • Melting electrolysis device for purifying sodium metal

    CN202755066U

  • Fused electrolysis device used for preparing metallic sodium

    CN202898560U

  • Device for preparing lithium by feeding back chlorine in internal circulating way and melting electrolysis

    CN203373435U